The relationship between human, social and financial capital and small and medium enterprise (SME) performance in South Africa - Siso, Masiso Nomakha (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The COVID-19 pandemic has had a severe impact on developing countries, exacerbating economic stagnation, high poverty rates, and unemployment. South Africa, in particular, faces significant challenges, with a 35.3 percent unemployment rate and a 17.4 percent GDP decline in 2021. Small and Medium Enterprises (SMEs) are crucial during these economic challenges, traditionally employing a substantial workforce and contributing significantly to the GDP. Despite their importance, SMEs often struggle, with a small percentage surviving the initial two years. Limited research has been conducted on the resources and capabilities crucial for enterprise performance in South Africa. While studies in developed countries exist, few explore the relationship between resources and capabilities facilitating SME performance in developing contexts. This study focuses on human capital, bonding, bridging, and linking social capital, and financial capital as key resources and capabilities. Given the backdrop that many entrepreneurs in South Africa may not possess formal education or extensive work experience, this study contends that financial literacy"”encompassing financial knowledge, behaviour, and attitude"”serves as a proxy for human capital. Additionally, a notable portion of entrepreneurs in South Africa face a deficit in the skills and knowledge essential for identifying entrepreneurial opportunities. Even among those possessing these capabilities, the challenge lies in the lack of necessary resources, including social and financial capital, to effectively transform such prospects into viable new ventures. This study employed a causal research design and adopted a quantitative research approach within a post-positivist paradigm. The primary objective was to investigate the relationship between the following independent variables; human (where financial literacy was used as a proxy which consisted of financial knowledge, attitude and behaviour), bonding, bridging and linking social capital, and financial capital and the dependent variable; SME performance. An online self-administered questionnaire was used to gather data from SME owners/managers. A pilot study was undertaken, in which an electronic link to the questionnaire was sent to potential respondents. Potential respondents were identified using purposive and convenience sampling methods. Data collection yielded 334 usable responses from SME owners/managers in South Africa. After cleaning the data, the analysis examined the relationship between independent and dependent variables. Confirmatory Factor Analysis (CFA) and Cronbach Alpha Coefficient analysis were used to confirm the validity and reliability of the measurement instrument, respectively. Descriptive statistics, regression, and correlation results were reported. Furthermore, a group mean analysis, including independent sample t-tests and one-way ANOVAs, were performed to investigate potential significant differences in variables based on demographic and enterprise related variables. The findings revealed a significant positive relationship between financial capital and SME performance. This indicates that an entrepreneur's ability to access financial capital or possess financial capital contributes to the performance and success of enterprises in South Africa. This finding underscores the crucial role of financial capital in facilitating the growth and sustainability of enterprises, as it provides a buffer against unfavourable economic shocks, enables entrepreneurs to pursue more capital-intensive strategies, and affords them more time to learn and overcome challenges. Conversely, no significant relationships were found between financial knowledge, behaviour, and attitude, bonding, bridging, and linking social capital, and SME performance. This study contributes to the development of SMEs in South Africa by identifying the critical resources and capabilities essential for their survival and growth. Additionally, it offers valuable recommendations for policymakers to create a conducive environment for entrepreneurs and suggests potential educational initiatives and support structures. Furthermore, this study advocates for the exploration of innovative financing approaches to build a financial cushion and bolster resilience against economic upheavals.
Keywords: Small business -- South Africa; Small and medium enterprises; Enterprise performance management; Financial literacy; Human capital; Social capital (Sociology); Financial capital; Resource-based view